HIGHER EDUCATION AND THE LABOUR MARKET IN UKRAINE: TRENDS AND CHALLENGES - Nataliia Mospan (Неперервна професійна освіта: теорія та практика)
In 2020 international and national economies have reached a milestone in their development. A new decade started with the COVID-19 pandemic, which hit the world economy and affected higher education and the labour market interaction. A national model of higher education interaction with the labour market has been shaped under the influence of global trends and challenges of the past decades, e.g. globalisation, marketisation, internationalisation and Europeanisation. The COVID-19 pandemic caused new transformations and digitalisation. The present study explores Ukraine’s higher education interaction with the labour market in the past decade. The research focuses on analysing the trends in higher education and the labour market in the pre-pandemic time. This interdisciplinary research integrates findings and perspectives from analytical reports, statistic data, and original surveys conducted in 2015 and 2020. The current state of play in the national higher education interaction with the labour market is described as an imbalanced model. It resulted in a supply and demand mismatch, a high unemployment rate of higher education graduates, educational and labour migration increase, and entrants’ reduction due to the demographic and economic crisis. It is concluded that on the eve of the COVID-19 pandemic, Ukraine gradually lost modern factors of economic growth – human and intellectual capital. In turn, the Coronavirus crisis caused new challenges – remote working, an emergency transition of higher education to a digitally-based format and online distance learning. These trends will likely widen the gap between national higher education and the labour market.